Strategi Pengembangan Pariwisata Melalui Program Masyarakat Berdaya Menuju Kota Pariwisata (Maya Juwita) Di Kecamatan Kepanjenkidul Kota Blitar - Edy Wasono; Eka Askafi (Universitas Islam Kadiri, 2020)
This research was conducted to know the development of Tourism Through the community Powerless To tourism (Maya Juwita) in district of Blitar Town Kepanjenkidul as a tourist Kampong. Methods of analysis used in this study is the analysis of the SWOT (Strength, Weakness, Opportunity, Threath). Results from this research menenunjukan a major starategi that needs to be done in order to materialize a tourist Kampong in district of Kepanjenkidul as a tourist area is divided into three main strategies, namely: Structuring the territory by establishing zoning for the activities of the community. Improvement of prowosi including conducts cultural tours. Counseling about the importance of the preservation of the environment, the mitigation of natural disasters and the dangers of pollution.